Pola Hidup Sehat dalam Islam di Masa Pandemi Covid-19: Studi Takhrij dan Syarah Hadis - Nada Hanif; Muhamad Yoga Firdaus; Multi Saridewi; Juni Ratnasari (Gunung Djati Conference Series, 2022)
This research aims to discuss the hadith of healthy lifestyles in Islam. This research uses a qualitative approach emphasized on library studies through the methods of takhrij and syarah hadith with contemporary analysis. The result of this research indicates that the hadith healthy lifestyles in islam particularly that taharah is the sahih quality of the throne of hadith so that it can be curated and used as dallary. Whereas syarah hadith indicates that a healthy lifestyle in Islam particularly that taharah is part of the faith so that taharah is important in Islam. Keeping clean and holy can be an effort to prevent the spread of Covid-19. The conclusion of the research, the hadith of healthy lifestyles in Islam and particularly the taharah is the shahih hadith, and keeping clean and holy, can prevent the spread of the Covid-19.